2017
DOI: 10.1080/10641963.2017.1407331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aquatic exercise on mental health, functional autonomy, and oxidative dysfunction in hypertensive adults

Abstract: The aquatic exercise is an effective non-pharmacological therapy for prevention and control of hypertension. The objective of the present study was to investigate the effect of aquatic exercise on mental health, functional autonomy, and oxidative dysfunction in hypertensive adults. Methodologically 29 adults (mean age 53 ± 7.5 years) were included in the study, and were randomly grouped as hypertensive (n = 16) and non-hypertensive (n = 13). Both groups underwent low-intensity aquatic exercise program for 12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
9
0
1
Order By: Relevance
“…In addition to certain diets [ 2 ], the practice of physical exercise can also increase antioxidant functions and protect the body against oxidative damage, through SOD enzymes (first route of defense against free radicals), CAT, GPx and GR [ 23 ], thus preventing premature aging. Some studies suggest that the regular practice of physical exercise [ 24 ], such as aquatic exercises [ 18 , 25 ], positively restores the vascular capacity in older and sedentary people and also improves anxiety, functional autonomy, and reduces oxidative stress and inflammation in hypertensive patients [ 25 ]. Da Silva and co-authors suggest that aquatic physical exercises should be considered as a common physical intervention for the control of arterial hypertension and other cardiovascular diseases and the improvement of the quality of life [ 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to certain diets [ 2 ], the practice of physical exercise can also increase antioxidant functions and protect the body against oxidative damage, through SOD enzymes (first route of defense against free radicals), CAT, GPx and GR [ 23 ], thus preventing premature aging. Some studies suggest that the regular practice of physical exercise [ 24 ], such as aquatic exercises [ 18 , 25 ], positively restores the vascular capacity in older and sedentary people and also improves anxiety, functional autonomy, and reduces oxidative stress and inflammation in hypertensive patients [ 25 ]. Da Silva and co-authors suggest that aquatic physical exercises should be considered as a common physical intervention for the control of arterial hypertension and other cardiovascular diseases and the improvement of the quality of life [ 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the physical properties and water temperature, these exercises contribute to the improvement and maintenance of the range of articulations movement, relaxation and reduction in muscle tension [ 17 ], improvement in cardiovascular functions and also in reducing pain [ 16 ]. According to Da Silva et al, in 2017, it was concluded that low-intensity aquatic exercise programs improve levels of oxidative stress, anxiety, functional autonomy, and inflammation in hypertensive patients and suggest that aquatic physical exercise should be considered as an common physical exercise intervention for the control of arterial hypertension and the improvement of the quality of life [ 18 ]. Water-based exercises have been shown to significantly increase the effectiveness of physical training in patients with chronic obstructive pulmonary disease [ 19 ] and a hydrotherapy session can reduce arterial stiffness in pregnant women with high-risk chronic arterial hypertension [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Water allows freedom of movement and the aquatic environment facilitates body movements that are limited by the force of gravity on land (Becker, 2009; Frye et al., 2017). By diminishing the influence of gravity and resistance to body motion, the literature has suggested that carrying out activities in the water allows training physical skills such as coordination, flexibility, or tolerance to exercise, promoting increased aerobic and cardiopulmonary output, and improving general physical condition (Becker, 2009; Da Silva et al., 2017; Frye et al., 2017; Waller et al., 2009). Furthermore, our program encouraged motor activity and exercise in the aquatic environment, in line with the available evidence on the physical health benefits of physical activity in people with mental illness (Richardson et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In people with SMI, the main objective is to optimize the daily functioning and well‐being, through the acquisition and improvement of psychosocial skills, the promotion of basic and instrumental daily life habits, and the participation in meaningful activities. Previous studies have concluded that the aquatic‐based interventions improve various domains of well‐being (e.g., happiness, anxiety, and self‐esteem) in people with disabilities and in groups with a chronic health condition (Aidar et al., 2018; Berlin et al., 2003; Da Silva et al., 2017; Driver et al., 2006; Hejazi et al., 2012; Neville et al., 2014; Silva et al., 2019; Tomas‐Carus et al., 2008). Despite these positive findings, however, research on the effects of the aquatic‐based programs among people with SMI is very scarce (Evans, 2017; Smith et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos demostram que os exercícios alteram sintomas de ansiedade (MCMAHON et al, 2017;WEGNER et al, 2014). Da Silva et al (2018) apontam que o exercício aquático de baixa intensidade reduz sintomas de ansiedade. Broocks et al (1998) revisaram a literatura sobre os efeitos neurobiológicos do exercício físico, sugerindo que existem evidências experimentais suficientes para apontar que o exercício regular induz a uma regulação de certos receptores serotoninérgicos centrais, que desempenham um papel importante na patogênese da ansiedade.…”
Section: Participantesunclassified